Microsoft mapping : geospatial development with Bing Maps and C♯ - Rischpater, Ray; Au, Carmen (Expert's voice in Microsoft., 2013)
Geospatial mapping applications have become hugely popular in recent years. With smart-phone and tablet numbers snow-balling this trend looks set to continue well into the future. Indeed, it is true to say that in today's mobile world location-aware apps are becoming the norm rather than the exception. In Microsoft Mapping author Ray Rischpater showcases Microsoft's Bing Maps API and demonstrates how its integration features make it by far the strongest mapping candidate for business that are already using Windows 8 or the .NET Framework. Whether you want to build a new app from scratch of add.